(untitled) (Journal of Plant Disease Sciences, 2024)
An efficient biosynthesis process for the rapid production of nanoparticles would enable the development of a “microbial nanotechnology” for mass-scale production. Silver nanoparticles (AgNPs) are extensively applied in multiple fields due to their strong antimicrobial activity and are considered alternatives to fungicides. Therefore, present in vitro study was planned to biosynthesis and characterization of silver nanoparticles from culture filtrates of Trichoderma spp. Trichoderma asperellum(T. viride), T. hamatum and T. harzianum were selected to synthesize silver nanoparticles.The culture filtrate of Trichoderma asperellum,T. hamatum and T. harzianum were used for the reduction of silver ions (Ag+) in AgNO solution to the3silver (Ag0) nanoparticles. The different ages (4 days, 6 days, 8 days, 12 days and 15 days) of culture filtrates were screened for the synthesis of silver nanoparticles. Synthesized silver nanoparticles were characterized using UV-Vis spectrophotometer and Transmission Electron Microscopy (TEM). Among the all treatments the silver nitrate solution treated with six days aged culture filtrate of Trichoderma sp. showed the UV absorption peak at 440 nm with maximum intensity after 24 hrs of incubation. The TEM micrographs showed the spherical shape silver nanoparticles with an average size range from T. asperellum silver nanoparticles07.09 to 12.18 nm, T. harzianum silver nanoparticles 08.45 to 15.03 nm and T. hamatum silver nanoparticles 22.93 to 35.66 nm.